Tobacco Use among Health Professional Students in Chitwan, Nepal - Shrestha, Niki; Shah, Sanjeeb; Khanal, Gayatri; Piryani, Suneel (Journal of Nepal Health Research Council, 2018)
Background: Health professional students play a critical role in tobacco control by providing services, advocating for policies and serving as role models for social change. This study aimed to estimate the prevalence of tobacco use and determine the attitude and behavior regarding tobacco use among health professional students.Methods: A cross-sectional study was conducted among third-year medical, dental, nursing and pharmacy undergraduates using GHPSS questionnaire. Results: A total of 16.3% students were current cigarette smokers. 33.2% students had ever smoked cigarettes, and 57.0% had smoked first cigarettes during adolescence life. Cigarette smoking consumption was higher than the use of other tobacco products like chewing tobacco, snuff, bidis, hookah, cigar or pipes and. 10.0%students were current users of other tobacco products.22.1%students had ever used other tobacco products.31.6% were exposed to second-hand smoke at home and 48.9% were exposed to second-hand smoke at public places. Conclusions: The prevalence of smoking and exposure to second-hand was high among medical students. Medical educators should consider revising the medical curricula to focus on tobacco cessation training/counseling in medical schools. Keywords: GHPSS;health professional; Nepal; tobacco.